TEACHING METHODS IN COMPUTER BASED LEARNING - KUDĚLKA, Miloš; MOŠOVÁ, Vratislava (Trends in education, 2009)
In our paper, we are focusing on working educational processes. We are inspired by different authors and try to find common features. These features can help teachers without a pedagogical graduation. In part, we are interested in computer based learning.
Keywords: microgenre; pedagogical pattern and antipattern; e-learning pattern.